Identifying history in servitude : A comparative study on the teaching of critical historical thinking in Finland, the United States, and China - Suominen, Olli (fi=Turun yliopisto|en=University of Turku|, 2021)
This study examines senior secondary level History education in three countries—Finland, the United States and China—from the vantage point of critical thinking skills. Critical historical thinking skills are a vast and ambiguous concept encompassing different kinds of factual knowledge and skills. For this reason, the focus of the study is on the teaching of the concept of history politics. History politics can be defined as the intentional “twisting and turning” —i.e. misinterpretation—of past events in order to further political ambitions. This kind of behavior can be understood as a central part of a larger toolbox of critical historical thinking skills. In particular, the work seeks to examine how and why education seeks to highlight the possibility of using history in this manner. When examining these choices made in the field of educational policy, the work sets off with the so-called political curriculum theories, which suggest, that the curriculum not only mirrors, but also constructs societal values and ambitions. When it comes to these ambitions, the focus of my work in particular is on the conflict between the so-called qualificative and integrative functions of education. This juxtaposition has been seen as the central question in the sociology of education. In other words, this study seeks to answer, whether the manner in which the concept of history politics is being taught offers students factual knowledge and skills, which allow them to survive in life (qualificative functions) or if the purpose of education is to further societal cohesion (integrative functions). This question is examined at different levels of the curriculum. In addition to comparisons made between geographical/cultural units and educational regimes, this study examines also temporal changes in educational policy when it examines whether there has been changes in these policies over time, and whether a global convergence is identifiable. Curriculum documents and school textbooks, as well as teacher interviews in the cases of Finland and the United States have been used as research materials. The temporal comparisons have been carried out by comparing textbooks from the mid-1980s and mid-2010s. The research material has been approached in an abductive manner by utilizing qualitative content analysis. The study reveals how the concept of history politics can be taught in numerous ways. On the one hand, a marked difference can be identified in whether the talk is clearly about history politics or in a much more ambiguous way about ideas, concepts and behavior, which are only tentatively linked to the concept of history politics. On the other hand, there were clear differences identifiable in the research material in terms of whether the concept is being taught at a theoretical/abstract level, or alternatively through concerete examples. Additionally, one can identify different kinds of concrete examples of the use of history politics, which are being highlighted. The different emphases between these approaches can be interpreted as furthering either the qualificative or integrative functions of education. In Finland the concept of history politics has been taught in senior secondary education rather extensively already in the 1980s, although by the 2010s even more viewpoints were covered. It is noticeable that closer to our time the concept of history politics is taught as part of the mandatory studies in particular, whereas the elective courses emphasize the issue much less. In the case of the United States it is worth noticing that already in the 1980s the concept of history politics has been cover in education to a degree, but no temporal change is identifiable. In addition, the study uncovered how the more demanding Advanced Placement courses, which are being offered to students, do not examine the concept any more thoroughly compared to the standard courses. In the cases of Finland and the United States the teacher interviews suggest, that at least when it comes to the teaching of the concept of history politics, the teachers have a quite a bit room for maneuverability, which they also gladly also use. For this reason, at the grassroots level education can further very different kinds of ambitions depending on the preferences of individual teachers. In China the concept of history politics has not been taught much previously, and arguably the goal of education was much more that of preserving societal cohesion rather than the cultivation of individual thinking skills. However, by the 2010s, the Chinese educational system had clearly taken steps towards emphasizing historical thinking skills. It is noticeable, however, that teaching about the concept of history politics in modern China is part of the elective, rather than the mandatory courses in senior secondary education. Additionally, the lack of teacher interviews in the case of China means that it is not possible to comprehensively assess how the ambitions layed out in curriculum documents and textbooks is actually put into action at the grassroots level. The culturally, politically and historically very different kinds of societies aim—at least when examined from the perspective of teaching the concept of history politics—at the cultivation of thinking skills rather than at the preservation of societal cohesion. However, different cultures, countries and educational regimes do not emphasize these qualificative functions of education equally strongly, and the temporal comparisons do not lend support to the notion about the global convergence of educational policy.

Tutkimuksessa vertaillaan kolmen maan – Suomen, Yhdysvaltojen sekä Kiinan – lukiotasoista historianopetusta kriittisten ajattelutaitojen opettamisen perspektiivistä. Kriittiset historian ajattelutaidot ovat erittäin laaja ja monitulkintainen kokonaisuus erilaisia tietoja ja taitoja. Tutkimuksen fokus on näin ollen rajattu niin kutsutun historiapolitiikan käsitteen opettamiseen. Historiapolitiikka voidaan määritellä toiminnaksi, jossa historian tapahtumia tarkoitushakuisesti ”käännetään ja väännetään” – siis väärintulkitaan – poliittisten intressien edistämiseksi. Kuvatun kaltaisen toiminnan ymmärtäminen voidaan nähdä keskeisenä osana laajempaa historian kriittisten ajattelutaitojen työkalupakkia. Nimenomaisesti työ hakee selvyyttä siihen, miten ja miksi koulutuksessa tuodaan esiin idea historian käytön mahdollisuudesta edellä kuvattuun tapaan. Näitä koulutuspoliitisia valintoja tutkiessaan työ lähtee teoreettisesti liikkeelle niin kutsutusta poliittisesta opetussuunnitelmateoriasta joka esittää, että opetussuunnitelma paitsi heijastelee, mutta myös rakentaa yhteiskunnallisia arvoja sekä tavoitteita. Näiden tavoitteiden osalta työni keskittyy erityisesti koulutuksen nk. kvalifikaatio- ja integraatiotehtävien väliseen ristiriitaan, joka on perinteisesti nähty koulutussosiologian keskeisimpänä kysymyksenä. Toisin sanoen työ hakee vastauksia kysymykseen, pyrkiikö tapa, jolla historiapolitiikan käsitettä opetetaan, tarjoamaan oppilaille erilaisia tietoja ja taitoja pärjätä elämässä (kvalifikaatiot), vai onko valitun lähestymistavan ensisijainen tarkoitus edistää yhteiskunnallista koheesiota (integraatio). Tätä problematiikkaa lähestytään opetussuunnitelman eri tasoilla. Maantieteellis-kulttuurillisen ja opetusjärjestelmäkohtaisen vertailun ohella työ tarkastelee myös koulutuspolitiikan ajallisia muutoksia tarkastellessaan kysymystä siitä, onko koulutuspolitiikan tavoitteissa havaittavissa ajan myötä tapahtunutta globaalia yhdenmukaistumista – konvergenssia. Analyysiaineistona työssä on käytetty opetussuunnitelmadokumentteja ja oppikirjoja, sekä Suomen ja Yhdysvaltojen tapauksessa lisäksi myös opettajahaastatteluita. Ajallinen vertailu on toteutettu 1980- sekä 2010-lukujen puolivälien oppikirjoja vertailemalla. Aineistoa on analysoitu laadullisen sisällönanalyysin keinoin, abduktiivisella tutkimusotteella. Tutkimuksesta käy ilmi, miten historiapolitiikan käsitettä voidaan opettaa hyvin erilaisilla tavoilla. Selviä jakolinjoja on nähtävissä yhtäältä siinä, puhutaanko opetuksessa selvästi historiapoliittisesta toiminnasta vaiko ympäripyöreästi ajatuksista, käsitteistä ja toiminnasta, joiden yhteys nimenomaisesti historiapoliittiseen toimintaan ei ole täysin selvä. Toisaalta tutkimusmateriaalin valossa on havaittavissa selviä eroja myös siinä, opetetaanko käsitettä teoreettisella tai abstraktilla tasolla, vai vaihtoehtoisesti konkreettisten esimerkkien kautta. Lisäksi eroja on havaittavissa siinä, millaisia konkreettisia esimerkkejä historiapolitiikan käytöstä nostetaan esiin. Näiden eri lähestymistapojen välisten painotusten voidaan tulkita tähtäävän joko koulutuksen kvalifikaatio- tai integrointitehtävien edistämiseen. Suomessa historiapolitiikan käsitettä on opetettu lukioissa jo 1980-luvun puolivälissä melko monipuolisesti, joskin 2010-luvulle tultaessa aiheen käsittely on monipuolistunut entisestään. Huomattavaa on kuitenkin se, että lähempänä omaa aikaamme historiapolitiikan käsitettä opetetaan erityisesti osana pakollisia historian opintoja, kun taasen valinnaisten kurssien yhteydessä käsitteen opetus painuu selvästi enemmän taka-alalle. Yhdysvaltojen tapauksessa huomionarvoista puolestaan on se, että historiapolitiikkaa on käsitelty ja käsitellään opetuksessa jonkin verran, mutta mitään ajallista muutosta ei aineistossa ole havaittavissa. Lisäksi tutkimuksessa selvisi, että vaikka oppilaille on nykyään tarjolla vaativampia Advanced Placement -kursseja, ei niiden opetustarjonta pureudu historiapolitiikan käsitteen opettamisessa perusmuotoisia kursseja syvemmälle. Suomen ja Yhdysvaltojen tapauksessa opettajahaastattelut muodostavat kuitenkin sen kuvan, että ainakin niiltä osin, mitä tulee historiapolitiikan käsitteen opettamiseen, on opettajilla aiheessa varsin mittavasti liikkumavaraa, jota he myös käyttävät. Näin ollen ruohonjuuritasolla käytännön opetus voi edistää hyvin erilaisia tavoitteita opettajan omista preferensseistä riippuen. Kiinassa ei historiapolitiikan käsitettä aiemmin juuri opetettu, ja voidaankin nähdä, että koulutuksen tehtävänä oli ennemminkin yhteiskunnallisen koheesion vaalinta kuin yksilön ajattelutaitojen kultivointi. 2010-luvulle tultaessa kiinalainen opetusjärjestelmäkin on kuitenkin selvästi ottanut askeleita historian ajattelutaitoja korostavampaan suuntaan. Huomattavaa on kuitenkin se, että historiapolitiikan opetus nyky-Kiinassa painottuu nimenomaisesti osaksi valinnaisten kurssien sisältöä. Lisäksi Kiinan tapauksessa ei opettajahaastattelujen puutteen vuoksi ole mahdollista tehdä erityisen pitkälle meneviä johtopäätöksiä siltä osin, miten opetussuunnitelmien ja oppikirjojen sisältö sekä tavoitteet realisoituvat ruohonjuuritason opetuksessa. Yleisemmällä tasolla voidaan kuitenkin sanoa, että vertailun alla olevat, kulttuurillisesti, poliittisesti ja historiallisesti hyvin erilaiset yhteiskunnat pyrkivät ainakin historiapolitiikan käsitteen opetuksen perspektiivistä tarkasteltuna historianopetuksessa ennemminkin ajattelutaitojen kultivointiin kuin yhteiskunnallisen koheesion vaalimiseen. Eri maailmankolkissa ei kuitenkaan missään nimessä anneta edellä mainitulle koulutuksen kvalifikaatiotehtäville samoissa määrin painoarvoa, eikä ajallinen vertailu anna tukea teorioille koulutuspolitiikan globaalista konvergenssista.